Polygon-based Landslide Inventory for Bandung Basin Using Google Earth - Sukristiyanti Sukristiyanti; Ketut Wikantika; Imam A. Sadisun; Lissa F. Yayusman; Jevon A. Telaumbanua (Indonesian Journal of Geography, 2021)
A landslide inventory representing landslide locations is used as a key factor in landslide susceptibility assessment. This paper explores Google Earth (GE) for generating a polygon-based landslide inventory in Bandung Basin. How far GE can identify landslides and their boundaries, source areas, and types were discussed here. Visual interpretation of GE images supported by path tool in GE, official landslide reports, previous research papers, and media was performed. The result is a polygon-based landslide inventory consisting of 194 landslide areas and 194 landslide source areas during 1993-2020. The limitations of GE in preparing the landslide inventory are (1) not covering the timing of the landslide occurrences, (2) tricky to identify small landslides (<100 m2) in anthropogenically transformed areas, and (3) not able to distinguish between earth and debris of landslide material.